2017
DOI: 10.1186/s41935-017-0008-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of latent fingerprints on non-porous surfaces recovered from fresh and sea water

Abstract: BackgroundCriminal offenders have a fundamental goal not to leave any traces at the crime scene. Some may suppose that items recovered underwater will have no forensic value, therefore, they try to destroy the traces by throwing items in water. These traces are subjected to the destructive environmental effects. This can represent a challenge for forensic experts investigating fingerprints.MethodsThe present study was conducted to determine the optimal method for latent fingerprints development on dry non-poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
1
22
0
1
Order By: Relevance
“…On top of that, the consistent inadequate quality of fingerprints recovered from immersed evidence continues to pose an uphill challenge, presumably due to the duration of immersion (Trapecar 2012;Rohatgi et al 2015;Rohatgi and Kapoor 2016) as well as different types of water (Rohatgi et al 2015). Such observation was also supported by Madkour et al (2017) whereby the authors reported on relatively poor performance of SPR in visualizing latent fingerprints on glass, metal and plastic surfaces, particularly after exposure to sea and lake waters in different aquaria for more than 24 h.…”
Section: Latent Fingerprints: Challenges and Future Insightsmentioning
confidence: 90%
“…On top of that, the consistent inadequate quality of fingerprints recovered from immersed evidence continues to pose an uphill challenge, presumably due to the duration of immersion (Trapecar 2012;Rohatgi et al 2015;Rohatgi and Kapoor 2016) as well as different types of water (Rohatgi et al 2015). Such observation was also supported by Madkour et al (2017) whereby the authors reported on relatively poor performance of SPR in visualizing latent fingerprints on glass, metal and plastic surfaces, particularly after exposure to sea and lake waters in different aquaria for more than 24 h.…”
Section: Latent Fingerprints: Challenges and Future Insightsmentioning
confidence: 90%
“…Madkour 45 found the Cyanoacrylate fuming technique to be the most suitable technique for items submerged in fresh and salt water for up to 10 days. 45 This disputes many other sources stating this technique cannot be used if the item have been wet. The longer the time before a fingerprint is treated, the higher the impact of degradation.…”
Section: Figurementioning
confidence: 99%
“…The longer the time before a fingerprint is treated, the higher the impact of degradation. 45 The components enhanced in cases regarding water submersion may be the components that are changed by the heat and may not be detectable after both exposures. For example, salt is able to withstand intense heat and is believed to be the most durable fingerprint component, however, it is water soluble so may be washed away if exposed to water during the extinguishing efforts.…”
Section: Figurementioning
confidence: 99%
“…44 This is useful to be aware of as the fingerprint may have not been initially damaged by the heat, however, may possibly be damaged if submerged in water until the investigation team attend the scene. Madkour 45 found the Cyanoacrylate fuming technique to be the most suitable technique for items submerged in fresh and salt water for up to 10 days. 45 This disputes many other sources stating this technique cannot be used if the item have been wet.…”
Section: Figurementioning
confidence: 99%
“…Water with a higher salinity value than fresh water has a more detrimental effect on the quality of the fingerprint obtained. 45 Some fingerprints will emit a weak luminescence. The source of this is unknown and believed to be from contamination to the natural eccrine secretion residues.…”
Section: Other Factors To Considermentioning
confidence: 99%